Study on physiological response of drought tolerant groundnut genotypes associated with different stress levels - Nge, Su Htwe; Khaing, Aye Aye; Oo, Htay Htay; Htwe, Nyo Mar; Win, Khin Myo; Thu, Aung Kyaw (Applied Research in Science and Technology, 2023)
Identification of drought tolerant genotypes with superior drought tolerant physiological traits is essential for the success of drought tolerance breeding program. This study was conducted to observe physiological response of drought tolerant groundnut genotypes associated with different stress levels. During 2021-2022 post-monsoon season, eight groundnut genotypes were evaluated under non-stress (field capacity), moderate stress (50 % available water) and severe stress (25 % available water) conditions. The experiment was undertaken using split plot design. Increasing drought stress levels decreased relative water content and increased canopy temperature and proline content. Total chlorophyll content increased under moderate stress condition and decreased under severe stress condition in some genotypes. The genotype ICGV-07235 and the drought tolerant check variety, Sinpadetha-12 showed consistent RWC values under different stress levels. The genotypes ICGV-07235, ICGV-07406 and Sinpadetha-12 possessed minimum canopy temperature values among the tested genotypes. Total chlorophyll content of the genotypes ICGV-07286 and ICGV-07235 were higher than that of the other tested genotypes. The genotypes ICGV-07390, YZG-07084 and ICGV-07286 had the highest proline content under stress conditions. Based on the results, the genotypes YZG-07084, ICGV-07286, ICGV-07235, ICGV-07390 and ICGV-07406 possessed desired physiological traits and these genotypes could be effectively utilized for developing drought tolerant groundnut genotypes.